2016
DOI: 10.1007/s00330-016-4419-y
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution T2-weighted cervical cancer imaging: a feasibility study on ultra-high-field 7.0-T MRI with an endorectal monopole antenna

Abstract: ObjectivesWe studied the feasibility of high-resolution T2-weighted cervical cancer imaging on an ultra-high-field 7.0-T magnetic resonance imaging (MRI) system using an endorectal antenna of 4.7-mm thickness.MethodsA feasibility study on 20 stage IB1–IIB cervical cancer patients was conducted. All underwent pre-treatment 1.5-T MRI. At 7.0-T MRI, an external transmit/receive array with seven dipole antennae and a single endorectal monopole receive antenna were used. Discomfort levels were assessed. Following i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…We have found that the use of an internal antenna in combination with an external array of radiating antennas provides sufficient SNR for MRI and STEAM MRS acquisitions at 7 T. The inclusion of internal antennas to enhance SNR in MRI has been already explored at lower magnetic field strengths to image the uterine cervix, with positive results, 15,19,20 and has been validated in this pilot study at the field of 7 T. The positive effect of this internal monopole antenna has been recently investigated at our institution for the same patient population. 27 In particular, the quality of the T2w MRI obtained for all patients was found to be superior to the T2w MRI routinely acquired at 1.5 T. 27 The MRS results found in this study agree with previous published MRS studies at lower magnetic field strengths, where mainly fatty acid signals were observed in uterine cervical ACs. 11,[14][15][16][17][18]36 The fatty acid oxidation pathway in cancer cells has been recently given more attention and proven to be as important in cancer metabolism as the Warburg effect.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We have found that the use of an internal antenna in combination with an external array of radiating antennas provides sufficient SNR for MRI and STEAM MRS acquisitions at 7 T. The inclusion of internal antennas to enhance SNR in MRI has been already explored at lower magnetic field strengths to image the uterine cervix, with positive results, 15,19,20 and has been validated in this pilot study at the field of 7 T. The positive effect of this internal monopole antenna has been recently investigated at our institution for the same patient population. 27 In particular, the quality of the T2w MRI obtained for all patients was found to be superior to the T2w MRI routinely acquired at 1.5 T. 27 The MRS results found in this study agree with previous published MRS studies at lower magnetic field strengths, where mainly fatty acid signals were observed in uterine cervical ACs. 11,[14][15][16][17][18]36 The fatty acid oxidation pathway in cancer cells has been recently given more attention and proven to be as important in cancer metabolism as the Warburg effect.…”
Section: Discussionsupporting
confidence: 86%
“…In vivo 1 H MRS of uterine cervical carcinomas at 7 T to measure fatty acid profiles has been shown to be feasible for the first time. We have found that the use of an internal antenna in combination with an external array of radiating antennas provides sufficient SNR for MRI and STEAM MRS acquisitions at 7 T. The inclusion of internal antennas to enhance SNR in MRI has been already explored at lower magnetic field strengths to image the uterine cervix, with positive results, and has been validated in this pilot study at the field of 7 T. The positive effect of this internal monopole antenna has been recently investigated at our institution for the same patient population . In particular, the quality of the T2w MRI obtained for all patients was found to be superior to the T2w MRI routinely acquired at 1.5 T …”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Based on this case series, the present results clearly illustrated that UHF MRI outperformed conventional MRI in terms of malignancy characterization, diagnosis and local extension. Advantages of UHF MRI have been already documented in the oncological field, especially in prostate cancer, brain, oesophageal or cervical tumors [28][29][30][31][32][33][34]. Nonpathological imaging of bowel has shown increased spatial resolution and interestingly better signal of vessels in abdomen, which seems to be confirmed on our images with clear delineation of vessels anatomical layers [35,36].…”
Section: Discussionsupporting
confidence: 75%